The Correlation Between Students’ Writing Self-Efficacy and Essay Writing Performance - Setyowati, Lestari; Sukmawan, Sony; Karmina, Sari; Mabaroh, Barotun (Universitas Pendidikan Mandalika, 2024)
Self-efficacy in writing is an important factor for a student-writer to accomplish a writing task. However, not all studies show that writing self-efficacy and writing achievement are positively related. The purpose of the study is to find out 1) the writing self-efficacy level of the second-year students of an English education study program in one of the private universities in Pasuruan Regency, East Java, Indonesia, and 2) the correlation between students’ writing self-efficacy and their writing performance. The research uses a correlational design. The sample of the research was fifty students of English study program from one of private universities in Pasuruan regency, Easyt Java, Indonesia. The instrument used to collect the data was the writing self-efficacy questionnaire developed by Prickel in 1994, test, Primary Trait Scoring (PTSG) rubric, and documentation of the student's essay. The questionnaire consists of 25 items about self-efficacy in writing with a five-point scale of answers. The result shows that the students’ self-efficacy level mainly falls in the moderate category (58%), while the rest fall in the high category (42%). The result of the correlation analysis shows that there is no correlation between the students’ writing self-efficacy and their writing achievement (r= -.020, n = 50, p = .892). The result implies that writing teachers should continuously foster their students' writing self-efficacy by giving them sufficient practice opportunities, offering constructive feedback, as well as providing emotional and psychological support in time of difficulties.